Realizing Awakened Consciousness Interviews with Buddhist Teachers and a New Perspective on the Mind. - Boyle, Richard P. (New York : Columbia University Press, 2015)
Richard Boyle was an associate professor of sociology at the University of California, Los Angeles, until 1972, when he left to pursue his studies in Buddhism in the mountains of northern New Mexico. Some years later, he moved to Albuquerque and worked as a senior research scientist at the University of New Mexico's Institute for Social Research. He is recently retired.
15. The Awakened Baby?16. The Human Condition and How We Got Into It; 17. Modeling Consciousness, Awakened and Ordinary; Appendix: Interview with James Austin, Neuroscientist; Notes; Glossary of Buddhist Terms; References; Index.
Print version record.
Includes bibliographical references and index.
ebrary DDA
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Enlightenment (Buddhism); Buddhists -- Interviews; Buddhists; Enlightenment (Buddhism); RELIGION / Comparative Religion; Electronic books; Interviews